The atherogenic effect of excess methionine intake - Troen, Aron M; Lutgens, Esther; Smith, Donald E; Rosenberg, Irwin H; Selhub, Jacob (Proceedings of the National Academy of Sciences - PNAS, 2003)
Methionine is the precursor of homocysteine, a sulfur amino acid intermediate in the methylation and transsulfuration pathways. Elevated plasma homocysteine (hyperhomocysteinemia) is associated with occlusive vascular disease. Whether homocysteine per se or a coincident metabolic abnormality causes vascular disease is still an open question. Animals with genetic hyperhomocysteinemia have so far not displayed atheromatous lesions. However, when methionine-rich diets are used to induce hyperhomocysteinemia, vascular pathology is often observed. Such studies have not distinguished the effects of excess dietary methionine from those of hyperhomocysteinemia. We fed apolipoprotein E-deficient mice with experimental diets designed to achieve three conditions: (i) high methionine intake with normal blood homocysteine; (ii) high methionine intake with B vitamin deficiency and hyperhomocysteinemia; and (iii) normal methionine intake with B vitamin deficiency and hyperhomocysteinemia. Mice fed methionine-rich diets had significant atheromatous pathology in the aortic arch even with normal plasma homocysteine levels, whereas mice fed B vitamin-deficient diets developed severe hyperhomocysteinemia without any increase in vascular pathology. Our findings suggest that moderate increases in methionine intake are atherogenic in susceptible mice. Although homocysteine may contribute to the effect of methionine, high plasma homocysteine was not independently atherogenic in this model. Some product of excess methionine metabolism rather than high plasma homocysteine per se may underlie the association of homocysteine with vascular disease.